An ancestry‐based approach for detecting interactions. Issue 1 (8th November 2017) - Park, Danny S.; Eskin, Itamar; Kang, Eun Yong; Gamazon, Eric R.; Eng, Celeste; Gignoux, Christopher R.; Galanter, Joshua M.; Burchard, Esteban; Ye, Chun J.; Aschard, Hugues; Eskin, Eleazar; Halperin, Eran; et al.
ABSTRACT: Background: Epistasis and gene‐environment interactions are known to contribute significantly to variation of complex phenotypes in model organisms. However, their identification in human association studies remains challenging for myriad reasons. In the case of epistatic interactions, the large number of potential interacting sets of genes presents computational, multiple hypothesis correction, and other statistical power issues. In the case of gene‐environment interactions, the lack of consistently measured environmental covariates in most disease studies precludes searching for interactions and creates difficulties for replicating studies. Results: In this work, we develop a new statistical approach to address these issues that leverages genetic ancestry, defined as the proportion of ancestry derived from each ancestral population (e.g., the fraction of European/African ancestry in African Americans), in admixed populations. We applied our method to gene expression and methylation data from African American and Latino admixed individuals, respectively, identifying nine interactions that were significant at P < 5 × 10 − 8 . We show that two of the interactions in methylation data replicate, and the remaining six are significantly enriched for low P ‐values ( P < 1.8 × 10 − 6 ). Conclusion: We show that genetic ancestry can be a useful proxy for unknown and unmeasured covariates in the search for interaction effects. These results have important implications for our understanding of the genetic architecture of complex traits.